The role of digital participation platforms in risk-informed development: A case study of Surabaya, Indonesia - Ronan McDermott; Saut Sagala; Nurulitha Andini Susetyo; Akhirul Insan; William Diondi Parasian Harahap; Annisaa Indrarini; Danang Azhari (Progress in Disaster Science)
There is growing policy consensus around the need for development to be risk-informed. In parallel, digital technologies are increasingly deployed to enhance participation within a wide range of policy domains, particularly in urban settings. While participation is considered essential to the timely and accurate identification and communication of risks with diverse stakeholders, the role of digital technologies with a participatory element in enabling risk-informed development is under-researched. This study identifies the factors that potentially enable digital participation platforms to contribute to risk-informed development based on an illustrative case study of Bulak District, Surabaya. Technology-related factors include the complementarity between digital platforms, citizen access to platforms, and aligned risk- and development -related policymaking and implementation processes. However, non-technological factors are equally, if not more, critical to digital participatory platforms' role in advancing risk-informed development. These include the risk awareness of participants, as well as the power relations that determine the design of such platforms and the ultimate translation into development planning of their outputs. Aligning regulatory frameworks for risk management and development, integrating digital tools at local and national levels, and improving the availability of disaster risk data are critical to digital participation platforms' role in promoting risk-informed development.